2012
DOI: 10.1021/jp211564x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of 1,2-Dimethoxyethane and 1,2-Dimethoxypropane through Phosphatidycholine Bilayers: A Molecular Dynamics Study

Abstract: In this paper, a theoretical study of 1,2-dimethoxyethane (DME) and 1,2-dimethoxypropane (DMP) at water/n-heptane and 1,2-dimyristoyl-sn-glycero-3-phospatidycholine (DMPC) lipid bilayer/water interfaces using the umbrella sampling method is reported. Recently proposed GROMOS96/OPLS compatible models for DME and DMP have been used for the simulation studies. The percolation free energy barrier of one DME and DMP molecule from water to n-heptane phase calculated using the umbrella sampling method turned out to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 60 publications
5
43
0
Order By: Relevance
“…(1) Small molecule conformational sampling [73][74][75][76]; (2) Protein-folding [77][78][79] and large-scale protein conformational sampling [80][81][82][83]; (3) Protein-protein/peptide-peptide interactions [84][85][86][87][88][89][90][91][92]; (4) DNA conformational changes [93] and DNA-DNA interactions [94][95][96]; (5) Binding and association free-energies [97][98][99][100][101][102][103][104][105][106][107]; (6) Adsorption on and permeation through lipid bilayers [108][109][110][111][112][113][114][115][116][117] …”
Section: Umbrella Samplingmentioning
confidence: 99%
“…(1) Small molecule conformational sampling [73][74][75][76]; (2) Protein-folding [77][78][79] and large-scale protein conformational sampling [80][81][82][83]; (3) Protein-protein/peptide-peptide interactions [84][85][86][87][88][89][90][91][92]; (4) DNA conformational changes [93] and DNA-DNA interactions [94][95][96]; (5) Binding and association free-energies [97][98][99][100][101][102][103][104][105][106][107]; (6) Adsorption on and permeation through lipid bilayers [108][109][110][111][112][113][114][115][116][117] …”
Section: Umbrella Samplingmentioning
confidence: 99%
“…The partition of a drug could be either predicted by long nano-second classical MDS, or by the Potential of Mean Force (PMF) methods (37,38). Using MDS on various fluorescent azaaromatic probes on water-membrane, it has been earlier shown that the probe localization is determined by the electrostatic dipole-dipole and van der Waals interactions (39).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations offer a valuable alternative to experiments, among which molecular dynamics method can be used to investigate the interactions between drug and model membrane, estimate its preferred position and predicate its permeability. Drug partitioning could be predicted by long-time traditional molecular dynamics, [2][3][4][5] or by potential of mean force (PMF) method that calculates the free energy profile of a drug along the bilayer normal [5,6], etc. We [7] have calculated the free energy profiles of three drugs with different permeability using PMF method, and the results show that the obtained energy barrier is correlated well with drug's permeability.…”
Section: Introductionmentioning
confidence: 99%